2019
DOI: 10.12688/f1000research.18039.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in vasoactive intestinal peptide physiology and pathophysiology: focus on the gastrointestinal system

Abstract: Vasoactive intestinal peptide (VIP), a gut peptide hormone originally reported as a vasodilator in 1970, has multiple physiological and pathological effects on development, growth, and the control of neuronal, epithelial, and endocrine cell functions that in turn regulate ion secretion, nutrient absorption, gut motility, glycemic control, carcinogenesis, immune responses, and circadian rhythms. Genetic ablation of this peptide and its receptors in mice also provides new insights into the contribution of VIP to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 120 publications
(168 reference statements)
1
91
0
6
Order By: Relevance
“…It was demonstrated that VIP plays a key role in the pathogenesis of inflammatory bowel syndrome (IBD) (Abad et al 2012). Infiltrates of immune cells and myofibroblasts VIP positive, have also been observed in the lamina propria as a response to the inflammatory state (Iwasaki et al 2019) (Figure 2). Immunofluorescence reactions of a-SMA (green signal) and VIP (red signal) confirmed immunoperoxidase method.…”
Section: Light Microscopy and Immunohistochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that VIP plays a key role in the pathogenesis of inflammatory bowel syndrome (IBD) (Abad et al 2012). Infiltrates of immune cells and myofibroblasts VIP positive, have also been observed in the lamina propria as a response to the inflammatory state (Iwasaki et al 2019) (Figure 2). Immunofluorescence reactions of a-SMA (green signal) and VIP (red signal) confirmed immunoperoxidase method.…”
Section: Light Microscopy and Immunohistochemical Analysismentioning
confidence: 99%
“…VIP is also expressed by immune cells, such as T cells, B cells, mast cells, eosinophils (Pozo et al 2000). It stimulates the secretion of HCO 3 -ions, acts on smooth muscles and plays a role as an anti-inflammatory mediator, regulating the abundance of cytokines, also inducing differentiation from Th cell to Th2 (Iwasaki et al 2019). VIP also is an inhibitor of gastric juice and promotes intestinal motility (Soares et al 2015;Wu et al 2015).…”
Section: Light Microscopy and Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, clinical and animal studies of intestinal permeability and vascular flow have not succeeded in identifying such mechanisms in cholera patients [ 21 ]. VIPergic pathways actually reduce epithelial paracellular permeability [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, elevations of cAMP after CT [ 26 ] or forskolin [ 27 ] are also associated with increased absorption of substrates of the active transport of sodium, such as glucose and glycine, suggesting that all or part of the cAMP elevation (or alterations in cAMP isoform variants) might represent a compensatory mechanism, aimed at overcoming the absorptive defect exemplified by the failure of absorption of plain saline solutions seen in cholera patients [ 28 ]. The mechanisms by which cAMP and VIP produce their effects are highly complex and beyond the scope of this report, but have been detailed in recent publications [ 22 , 29 ].…”
Section: Introductionmentioning
confidence: 99%